Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Accelerated Forced Degradation of Therapeutic Peptides in Levitated Microdroplets - Yangjie Li; Yanyang Hu; David L. Logsdon; Yong Liu; Yuejie Zhao; R. Graham Cooks (Pharmaceutical Research, 2020)

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Effect of the duration of inoculum exposure on development of citrus canker symptoms on seedlings of Swingle citrumelo - Clive H. Bock; James H. Graham; Tim R. Gottwald; Amanda Z. Cook; Paul E. Parker (European Journal of Plant Pathology, 2014)

Reconciling estimates of the contemporary North American carbon balance among terrestrial biosphere models, atmospheric inversions, and a new approach for estimating net ecosystem exchange from inventory‐based data - Daniel J. Hayes; David P. Turner; Graham Stinson; A. David McGuire; Yaxing Wei; Tristram O. West; Linda S. Heath; Bernardus de Jong; Brian G. McConkey; Richard A. Birdsey; Werner A. Kurz; Andrew R. Jacobson; et al. (Global Change Biology, 2012)
We develop an approach for estimating net ecosystem exchange ( NEE ) using inventory‐based information over North America ( NA ) for a recent 7‐year period (ca. 2000–2006). The approach notably retains information on the spatial distribution of NEE , or the vertical exchange between land and atmosphere of all non‐fossil fuel sources and sinks of CO 2 , while accounting for lateral transfers of forest and crop products as well as their eventual emissions. The total NEE estimate of a −327 ± 252 TgC yr −1 sink for NA was driven primarily by CO 2 uptake in the Forest Lands sector (−248 TgC yr −1 ), largely in the Northwest and Southeast regions of the US, and in the Crop Lands sector (−297 TgC yr −1 ), predominantly in the Midwest US states. These sinks are counteracted by the carbon source estimated for the Other Lands sector (+218 TgC yr −1 ), where much of the forest and crop products are assumed to be returned to the atmosphere (through livestock and human consumption). The ecosystems of Mexico are estimated to be a small net source (+18 TgC yr −1 ) due to land use change between 1993 and 2002. We compare these inventory‐based estimates with results from a suite of terrestrial biosphere and atmospheric inversion models, where the mean continental‐scale NEE estimate for each ensemble is −511 TgC yr −1 and −931 TgC yr −1 , respectively. In the modeling approaches, all sectors, including Other Lands, were generally estimated to be a carbon sink, driven in part by assumed CO 2 fertilization and/or lack of consideration of carbon sources from disturbances and product emissions. Additional fluxes not measured by the inventories, although highly uncertain, could add an additional −239 TgC yr −1 to the inventory‐based NA sink estimate, thus suggesting some convergence with the modeling approaches.

Wind speed and wind-associated leaf injury affect severity of citrus canker on Swingle citrumelo - C. H. Bock; James H. Graham; Tim R. Gottwald; Amanda Z. Cook; Paul E. Parker (European Journal of Plant Pathology, 2010)

Relationship Between the Endophyte Embellisia spp. and the Toxic Alkaloid Swainsonine in Major Locoweed Species (Astragalus and Oxytropis) - M. H. Ralphs; R. Creamer; D. Baucom; D. R. Gardner; S. L. Welsh; J. D. Graham; C. Hart; D. Cook; B. L. Stegelmeier (Journal of Chemical Ecology, 2008)

Physiological and performance effects of pyridostigmine bromide in healthy volunteers: a dose-response study - Mary R. Cook; Charles Graham; Antonio Sastre; Mary M. Gerkovich (Psychopharmacology, 2002)